2001
DOI: 10.7589/0090-3558-37.3.556
|View full text |Cite
|
Sign up to set email alerts
|

Altered Predation Susceptibility of Mosquitofish Infected With Eustrongylides Ignotus

Abstract: Eustrongylides ignotus is a parasitic nematode whose definitive hosts are often piscivorous wading birds (Ciconiiformes). Several species of small fishes are intermediate hosts, while larger predatory fish may be paratenic (transport) hosts. We examined predation susceptibility of infected mosquitofish (Gambusia holbrooki) to three species of predatory fishes, including juvenile largemouth bass (Micropterus salminoides), warmouth (Lepomis gulosus), and bluegill (Lepomis macrochirus). A 250 L aquarium with remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…The avian definitive hosts become infected when they consume the fish, thus completing the life cycle. This parasite causes pathology in piscivorous fish hosts and renders smaller forage fish more susceptible to predation (Coyner et al, 2001). In addition, the parasite causes significant mortality among nestling birds.…”
Section: Impacts On Hosts and Communitiesmentioning
confidence: 99%
“…The avian definitive hosts become infected when they consume the fish, thus completing the life cycle. This parasite causes pathology in piscivorous fish hosts and renders smaller forage fish more susceptible to predation (Coyner et al, 2001). In addition, the parasite causes significant mortality among nestling birds.…”
Section: Impacts On Hosts and Communitiesmentioning
confidence: 99%
“…In both cases, fish may be a source of infection for piscivorous birds and marine mammals FAGERHOLM, 1995;ANDERSON, 2000). In parasitism involving Eustrongylides sp., the definitive hosts are piscivorous birds; while in infections with Contracaecum sp., fish participate as the second intermediate hosts and contamination occurs after ingestion of parasitized oligochaetes (COLE, 1999;COYNER et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Holmes and Bethel [28] and Lafferty and Morris [31] studied that the parasitic infection reduces host stamina and locomotive efficiency. Coyner et al [9] showed that mosquitofish infected with parasite (Eustrongylides ignotus) and probably produce a physical and metabolic burden that may reduce and inhibit the fish's ability to avoid capture.…”
Section: Model Formulationmentioning
confidence: 99%